DEVELOPMENT OF COMMUNICATION SKILLS AMONG STUDENTS OF TECHNICAL UNIVERSITIES - Djurayeva , Nilufar Baxtiyarovna (Educational Research in Universal Sciences, 2023)
The article discusses the communication skills that teenagers who enter universities after completing their basic general education possess and the potential for developing these skills while attending an university using active and interactive learning techniques. Certain professions where the main spread of involvement communication place high demands on these people’s skills. In this article mentioned that human communication skills are important for communication, psychological society and social realization.